Development of Phonic Song Methods to Improve Articulation Ability in Speech Delay Children - Endang Rusyani; Imas Diana Apilia; Yeni Anggraeni; Dwi Fitria Al Husaeni (Universitas Pendidikan Indonesia (UPI), 2022)
Early-age childhood language skills are a benchmark for other developmental abilities. Children can express their desires and thoughts to the surrounding environment with expressive language. One of the barriers to expressive language is the difficulty of articulating consonants. This study aims to formulate a product in the form of developing a phonic song method to improve the articulation ability of children with speech delay. The Research and Development (RnD) research design was used in this study. RnD with a qualitative approach explores information about the objective condition of the subject. A quantitative approach using the Single Subject Research (SSR) experimental method with an A-B-A design to measure the effect of the phonic song method applied to the subject. The research was conducted in three stages, namely (i) preliminary study; (ii) phonics song program preparation, and (iii) phonic song program trial. The results of the study showed an increase in articulation ability in the pronunciation of these phonemes. The pronunciation of the phonemes /l/ and /k/ has increased from phase A1, from abilities 0-8 to 23-27. The pronunciation of the phonemes /g/ has changed from phase A1, from abilities 0-5 to 10 – 16, as well as from phases B and A2. The ability to pronounce the phoneme /s/ changed from phase A1, from abilities 4-12 to 22-24. The increase in ability occurred after receiving an intervention in the form of accompanying phonic song singing. Thus, it is hoped that this research can be a theoretical study in developing methods to improve the articulation of children with speech delay.